Some Thoughts on Trust and Betrayal. Issue 5 (3rd September 2018) - Bach, Sheldon
Abstract : Reacting to a general distrust of government and authority that many people are feeling these days, this paper follows some developments of trust and of its betrayal in both the normal and clinical situations. It suggests that many are profoundly anxious about betrayal and that adequate parenting helps us learn how to overcome inevitable betrayal traumas and continue without losing hope. It recalls Freud's own feelings of betrayal when he learned that hysterics lie and later when Dora stopped treatment, and it suggests that these betrayals may have been one factor in his turn from the clinical to the theoretical. It discusses trust in the clinical situation through the lens of the Freud–Ferenczi controversy and with special emphasis on early trauma and the kind of setting that may be necessary for the reestablishment of basic trust.